Bank Capital and Value in the Cross-Section - Mehran, Hamid; Thakor, Anjan (Review of Financial Studies, 2011)
[We develop a dynamic model of bank capital structure in an acquisitions context which predicts: (i) total bank value and the bank's equity capital are positively correlated in the cross-section, and (ii) the various components of bank value are also positively cross-sectionally related to bank capital. Our empirical tests provide strong support for these predictions. The results are robust to a variety of alternative explanations—growth prospects, desire to acquire toe-hold positions, desire of capital-starved acquirers to buy capital-rich targets, market timing, pecking order, the effect of banks with binding capital requirements, Too Big To Fail, target profitability, risk, and mechanical effects.]